STRATEGI PENGEMBANGAN AGRIBISNIS LADA HITAM LAMPUNG - Dian Rahmalia; Wan Abbas Zakaria; Teguh Endaryanto; Lidya Sari Mas Indah; Amanda Putra Seta; Erwanto Erwanto (Lampung University, 2023)
Pepper is a type of spice that has a slightly bitter, spicy, and warm character. Based on market forecasts, the trend of pepper consumption will continue to increase during the period from 2019 to 2025. In the domestic market, pepper has the potential to continue to be developed due to the opportunity to increase its consumption. However, pepper agribusiness also experiences various problems including limited ability to adopt seed technology, cultivation, and processing, lack of farmer capital, pest, and disease attacks, fluctuations in world prices, and lack of farmers who master technology. Therefore, it is necessary to analyze the pepper agribusiness development strategy, especially in Lampung with its product which is well known in the global market, namely Lampung black pepper. The purpose of this study was to formulate a strategy for developing black pepper agribusiness in Lampung Province through the identification of internal and external strategic factors. The research was conducted in Lampung Province in 2018. The research was conducted using FGD and survey techniques. Determination of the sample is done purposively. The sample comes from pepper agribusiness actors, polipolicymakersd pepper experts.This study uses descriptive qualitative and quantitative methods with SWOT analysis. Based on the results of the analysis, it is known that the position of black pepper agribusiness in Lampung Province is in group V with the position of the hold and maintain strategy. Strategy formulation is carried out on strengthening the basis of strength (S) and opportunity (O). The resulting strategy formulation includes policies and regulations including market certainty and price policy, strengthening human resource capacity, institutional and partnership development, technological innovinnovation, strengthening agro-input systems.Keywords: Agribusiness, Black pepper, Strategy development, Technological innovation